PEMBUATAN APLIKASI BIMBINGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (ABTIK) BERBASIS WEB DI SMAN 1 PENGASIH - Nurkhoiriyah Nurkhoiriyah (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The current teaching and learning process cannot be separated from the development of information and communication technology. In the curriculum of 2013, information and communication technology teachers have new tasks as a guidance teachers who provide guidance to students, as well as a subject teachers, and as an education staff to support the collegue when experiencing difficulties in terms of utilization of information and communication technology in the implementation of learning. Considering that there are a lot of school people in SMAN1 Pengasih including the number of teachers in 54 subjects, 598 students, and 18 staffs, the information and communication technology teachers look for alternatives of technical guidance by creating the Web-based Information and Communication Technology Guidance Application (ABTIK). The ABTIK guidance application implemented by making a flowchart, database structure, input design, and output design. The manufacturing procedure starts with the installation of php web server and MySQL database, preparing the database, making projects and hosting to the server. The ABTIK guidance application was able to bridge the information and communication technology guidance teachers and subject teachers, as well as education staff and students in real time so that teaching and learning activities can run well.